Are Candida albicans isolates from the oral cavity of HIV-infected patients more virulent than from non-HIV-infected patients? Systematic review and meta-analysis. (December 2020) - Orlandini, Renata Klemp; Bepu, Davi Ariel Nobuo; Saraiva, Maria da Conceição Pereira; Bollela, Valdes Roberto; Motta, Ana Carolina Fragoso; Lourenço, Alan Grupioni
Abstract: Candida albicans is the main causative agent of oral lesions in HIV-infected patients and its oral colonization is a potential source of systemic dissemination. Although the high prevalence of lesions in HIV patients can be explained by the immunosuppressive condition, several studies have reported that natural selection can make C. albicans more virulent in this group of patients. Comparisons of the activity of exoenzymes (phospholipase, proteinase and hemolysin) in C. albicans isolated from HIV-infected and uninfected patients have yielded conflicting results. This study aimed, through a systematic review and meta-analysis, to answer the question: "Is the hydrolytic enzymatic activity of C. albicans, isolated from the oral cavity, different in individuals infected and not infected with HIV?" The question was addressed using the PECO framework: P (Population): children and adults, E (Exposure): HIV infection, C (Comparator): non-HIV-infected patients; O (Outcomes): exoenzymes activity i.e. phospholipase, proteinase and hemolysin. We conducted a systematic search on Pubmed, Embase, Scopus, Livivo, Lilacs, Web of Science, and Science Direct databases, and Google Scholar. The MAStARI tool was used to evaluate the risk of bias in the selected studies. From 2259 studies, 19 were included in this review and 11 comprised the meta-analysis. The activity of phospholipase (M-H = 0.15; Z = 2, 76; p = 0.0006) and hemolysin exoenzymes (M-H = 0.07; z = 1, 94; p = 0.05) was higher in C. albicans isolated from the oral cavity of HIV-infected patients, whereas the levels of protease activity were not different compared with non-HIV-infected individuals. This study showed a higher phospholipase and hemolysin activity in C. albicans isolates from the oral cavity of HIV-infected patients. Highlights: Phospolipase activity is higher in C. albicans isolates from HIV-patients. Similar protease activity of C. albicans detected in HIV- and non-HIV-patients. . High frequency of positive hemolysin activity in C. albicans isolated from HIV-patients.